The life and Diversity of Kind of Bee in Gunung Walat Education Forest - Yoyo Ontaryo Purawidjaja; E.K.S Harini Muntasib (Media Konservasi, 1989)
Beekeeping development in Indonesia is supported either by the presence of many bee species which have a high potential to produce honey and many flowering plant species. Moreover, beekeeping has long been introduced as an attempt to increase human welfare, especially to those who live in and around forest areas.Gunung Walat, approximately 45 km south from Bogor and 15 km west from Sukabumi, has a high feasibility to develop beekeeping effort due to occurrence of flowering plant species known as bee food source, among others : Schima noronhea, Calliandra cdothyrsus, Lagerstroemia speciosa, Tectona grandis, Hibiscus tiliaceus, Paraserianthes fdcataria and Cassia siamea. The species of Bees which be found in Gunung Walat : Apis indica, Anfhophoro Iatreille, Megapis dorsata, Xylocopalatipese, Velutina keyensis, Eumenenes arenatus and Sreus amboinensis.